Comparison of frozen section accuracy with final pathology results in early clinical stage of endometrioid type endometrial cancer - Özgen, Levent; Özgen, Gülten (The European Research Journal, 2023)
Objectives: We aimed to compare the accuracy of the depth of myometrial invasion determined by intraoperative frozen section in the early clinical stage of endometrioid type endometrial cancer, with the result of the final postoperative paraffin section. Methods: The study was carried out with 102 patients who were diagnosed with type 1-2 endometrioid endometrial cancer in the gynecology clinic of the state hospital between January 2015 and 2019. Retrospective demographic data, clinical characteristics, and pathology results of the patients who underwent surgical staging were recorded. Results: The mean age of the patients was 59.3 ± 9.1 years and 82.3% of the patients were in the postmenopausal period. The mean age of patients with a depth of myometrial invasion<1/2 was lower than myometrial invasion>1/2, which was statistically significant (p < 0.001). According to the final postoperative pathology results, 93.1% (n = 95) of the cases were diagnosed as FIGO stage 1. The subgroups were 66.7% stage 1a and 26.4% stage 1b. When the stage and grade distribution was made according to the final postoperative pathology result, stage 1a grade 2 endometrial cancer was the most common with a rate of 43.1%. Concordance of the intraoperative and postoperative pathology results for the depth of myometrial invasion was 84.3%, the specificity was 100%, the positive predictive value was 100%, and the negative predictive value was 86.76%. Conclusions: The accuracy of the intraoperative frozen section in endometrial cancers is quite higher. For this reason, intraoperative pathological examination results are important in terms of minimizing the complications of unnecessary surgery.